Did the introduction of the euro lead to money illusion? Empirical evidence from Germany - Benjamin Bittschi; Saskia Duppel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
Using the introduction of the euro as a natural experiment, we provide economy-wide evidence for money illusion based on declared donations from German administrative income tax data. Our results suggest a magnitude of the money illusion effect between 2.4% and 7.6%. Compared to previous studies on money illusion in the course of the euro currency changeover this effect size is significantly lower. We trace this back to the more comprehensive donation data in our study compared to hitherto studied face-to-face collections, which makes our results less prone to "power of the ask" and social pressure effects.
urn:nbn:de:bsz:180-madoc-397036
Keywords: D12; E03; E40; 330; money illusion; euro introduction; charitable giving; natural experiment